2017
DOI: 10.1002/jcp.26017
|View full text |Cite
|
Sign up to set email alerts
|

Intimate connections: Inositol pyrophosphates at the interface of metabolic regulation and cell signaling

Abstract: Inositol pyrophosphates are small, diffusible signaling molecules that possess the most concentrated three-dimensional array of phosphate groups in Nature; up to eight phosphates are crammed around a six-carbon inositol ring. This review discusses the physico-chemical properties of these unique molecules, and their mechanisms of action. Also provided is information on the enzymes that regulate the levels and hence the signaling properties of these molecules. This review pursues the idea that many of the biolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
165
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(169 citation statements)
references
References 111 publications
(223 reference statements)
3
165
1
Order By: Relevance
“…The immediate target(s) of IP8 in eliciting the effects we describe here are as yet unknown. Two distinct themes have been invoked previously to account for IPP effects, whereby IPPs either: (i) bind to target proteins and allosterically enhance or inhibit their functions; or (ii) serve as phosphate donors for transfer of an IPP bphosphate to a previously mono-phosphorylated protein target leading to a covalent pyrophosphate modification of the target (34)(35)(36)(37). Potential mechanisms for IP8 to promote 3'processing/termination include: (i) allosteric binding or covalent modification of the processing/termination machinery so as to enhance its action on elongating Pol2; (ii) allosteric interaction with, or covalent modification of Pol2 to make it more responsive to the processing/termination machinery.…”
Section: Discussionmentioning
confidence: 99%
“…The immediate target(s) of IP8 in eliciting the effects we describe here are as yet unknown. Two distinct themes have been invoked previously to account for IPP effects, whereby IPPs either: (i) bind to target proteins and allosterically enhance or inhibit their functions; or (ii) serve as phosphate donors for transfer of an IPP bphosphate to a previously mono-phosphorylated protein target leading to a covalent pyrophosphate modification of the target (34)(35)(36)(37). Potential mechanisms for IP8 to promote 3'processing/termination include: (i) allosteric binding or covalent modification of the processing/termination machinery so as to enhance its action on elongating Pol2; (ii) allosteric interaction with, or covalent modification of Pol2 to make it more responsive to the processing/termination machinery.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that these domains act as cellular receptors for inositol pyrophosphate (PP-InsP) signaling molecules (Wild et al, 2016). PP-InsPs are composed of a fully phosphorylated inositol ring containing one or two pyrophosphate moieties (Shears, 2018). PP-InsPs bind to a basic surface cluster highly conserved among SPX domains to regulate divers biochemical and cellular processes in fungi, plants and animals.…”
Section: Introductionmentioning
confidence: 99%
“…Inositol pyrophosphates are derivatives of myo-inositol characterized by the presence of one or more diphosphates in addition to monophosphates around the inositol ring (1). These small molecules are found in all eukaryotic cells, and are involved in the regulation of many cellular processes, including energy and phosphate metabolism, DNA repair, ribosome biogenesis, vesicle trafficking and insulin secretion (1)(2)(3)(4)(5). In mammals, the most abundant inositol pyrophosphate is 5-diphosphoinositol pentakisphosphate (5-PP-IP5 or 5-IP7), which is synthesized from inositol hexakisphosphate (IP6) by IP6 kinases.…”
Section: Introductionmentioning
confidence: 99%